Watershed health assessment using the pressure–state–response (PSR) framework - Hazbavi, Zeinab; Sadeghi, Seyed Hamidreza; Gholamalifard, Mehdi; Davudirad, Ali Akbar (Land degradation & development, 2020)
A pressure–state–response framework was customized to outline the watershed health (WH) concept. To achieve this, the watershed indicators of pressure, state (S), and response (R) were conceptualized according to 17 climatic, anthropogenic, and hydrologic criteria. Four node years of 1986, 1998, 2008, and 2014 were selected to provide a running picture of the Shazand Watershed condition. The WH index was then calculated using geometric mean of pressure, S, and R indicators and assigned a range of values varied from 0 (unhealthiest) to 1 (healthiest). (a) The main pressures on the Shazand Watershed come from climatic factors in 1998 and 2008 and human factors in all study years. (b) The climatic factor and then anthropogenic factors had the maximum effectiveness in explaining the S indicator. (c) In calculating R indicator, the anthropogenic factors in 1986 and the hydrologic factors in other study years played significant contributions. (d) The greatest percentage of the study area were assigned to moderate condition of S indicator in 1986, 1998, and 2008 with value of 42, 46, and 73%, respectively, whereas in 2014, 44 and 42% of the watershed were respectively recognized as relatively healthy and moderately healthy in terms of S indicator. (e) For the first to fourth study node years, some 53, 77, 78, and 60% of the Shazand Watershed had the relatively unhealthy condition, respectively. (f) The Shazand WH decreased about 12% during periods of 1986–1998 and 1986–2008. (g) An improving trend was also found in WH for some sub‐watersheds.